ChemInform Abstract: Total Synthesis of Bicyclic Depsipeptides Spiruchostatins C and D and Investigation of Their Histone Deacetylase Inhibitory and Antiproliferative Activities. Issue 27 (13th June 2013) - Narita, Koichi; Fukui, Yurie; Sano, Yui; Yamori, Takao; Ito, Akihiro; Yoshida, Minoru; Katoh, Tadashi
Abstract Spiruchostatins C (Ia) and D (Ib) possess extremely potent inhibitory activities against cyclic depsipeptide histone deacetylase 1, better than previously known spiruchostatins A and B and the clinically approved depsipeptide FK228.